Overcoming the Negative Impacts of Social Media through Time Management for Vocational High School Students in South Jakarta - Dini Wahdiyati; Said Romadlan; Hendri Prasetya; Ratih Novita Sari (LPPM UIKA Bogor, 2023)
Social media is a new medium used by people to connect through the creation and exchange of information in a virtual network. As a medium of social interaction, social media has many benefits such as getting new information, entertainment, self-existence, and self-actualization. But on the other hand, social media also causes negative impacts such as information overload, hoaxes or false information, dependence, and addiction. For students, social media can be used as a means of learning and making friends, but the problem is that most students use social media for other things such as looking for pleasure, entertainment, and escape. Excessive use of social media by students will have an impact on decreasing learning achievement, therefore it is necessary to be given knowledge and understanding of time management to use social media. This community partnership program offers solutions on how to manage time in using social media so that it can benefit the self-development and learning achievement of students of SMK Al Falah, Mampang Prapatan. The results of this training show that good time management can reduce the negative impact of social media, and can increase productivity, and learning achievement, and develop students' talent.